(untitled) (Jurnal Destinasi Pariwisata, 2026)
This research aims to determine the current state of the products there and develop product marketing strategies. Observation, interview with managers, Pokdarwis, and related party interviews were conducted using a qualitative descriptive approach. The SWOT Analysis method was used for data analysis. The findings show that Munggu Tourism Village could have traditional tourism (like visiting Mekotek), natural tourism (like trekking through rice fields and going to Munggu Beach), cultural tourism (like dancing, painting, and traditional swings), and artificial tourism (like cooking classes, Beji Melukat Park, and tubing on the Penet River). According to TALC, Munggu Tourism Village is still in the development stage requiring special attention regarding conditions according to the life cycle of the tourism area. Therefore, Munggu Tourism Village needs an effective marketing plan to boost tourism and foster social networks and collaboration. The current tourism potential is not being fully utilized to increase visits and create economic benefits for the local community because the marketing strategy is not sustainable and integrated. This is evident from the product and other elements like price, place, promotion, people, process, and tangible evidence when combined with the Marketing Mix (7P). The Munggu Tourism Village product, which boasts a variety of tourism village products and a strategic location, is shown to have strengths, weaknesses, opportunities, and threats in a SWOT analysis. However, there are weaknesses and threats that occur.